Investigation of the Potentials of the Use of Termite Mould In Brick Production - Olu-Martins, O. A.; Alake, O.; Okechukwu, A. K.; Oluwasanya, T. (Journal of Science, Technology and Innovation Research, 2026)
The article discloses the results of the research, which was made on the resources of the termite mould as the building material, and compares its characteristics and application to the traditional ones (sand, and cement). The main materials that were used in the experiment were sand, termite mould, cement and water. The termite mould was used to make three sample mixtures with different proportions (termite mould only, 1:4 termite mould to sand and 4:1 termite mould). Findings indicated that the sample prepared using termite mould (sample 1) had the least water content (6.25 percent), reduced absorption rate (four voids after drying) and the specific gravity of 2.5. Conversely, the sample (3) that had termite mould and cement had the highest water content (15.63%). The sample composed of termite mould and cement (sample 3) demonstrated the highest compressive strength, reaching 24.42 MPa after 28 days of curing. The research has presented practical implications that the research of termite mould soil as a construction material showed that it could be used to produce environmentally friendly and thermally efficient bricks with average compressive strength. Meanwhile, to be practical in the contemporary construction, it requires either the refinement of the consistency of the brick production process and a better material enrichment (addition of more cement or sand).